2008
DOI: 10.4137/aci.s1005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gas Chromatography-Mass Spectrometry and Gas Chromatography-Tandem Mass Spectrometry with Electron Ionization and Negative-Ion Chemical Ionization for Analyses of Pesticides at Trace Levels in Atmospheric Samples

Abstract: A comparison of detection limits of gas chromatography-mass spectrometry (GC-MS) in selected ion monitoring (SIM) with gas chromatography-tandem mass spectrometry (GC-MS/MS) in selected reaction monitoring (SRM) mode with both electron ionization (EI) and negative-ion chemical ionization (NCI) are presented for over 50 pesticides ranging from organochlorines (OCs), organophosphorus pesticides (OPs) and pre-emergent herbicides used in the Canadian prairies (triallate, trifl uralin, ethalfl uralin). The develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 35 publications
1
48
0
5
Order By: Relevance
“…In general NCI-SIM provided the lowest method detection limits (MDLs) for the largest number of pesticides along with confirmation at these low levels. When confirmation by NCI-SIM was not sufficient, NCI-SRM could be used and gave additional sensitivity and confirmation ability to ~14% of pesticides studied (Raina and Hall, 2009). Others have also found that GC-MS/MS can provide added selectivity (Zhang and Lee, 2006).…”
Section: Gc/ms and Gc/ms/ms Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In general NCI-SIM provided the lowest method detection limits (MDLs) for the largest number of pesticides along with confirmation at these low levels. When confirmation by NCI-SIM was not sufficient, NCI-SRM could be used and gave additional sensitivity and confirmation ability to ~14% of pesticides studied (Raina and Hall, 2009). Others have also found that GC-MS/MS can provide added selectivity (Zhang and Lee, 2006).…”
Section: Gc/ms and Gc/ms/ms Methodsmentioning
confidence: 99%
“…OC degradation products have been routinely included in GC/MS methods either with EI or NCI and include OCs such as endosulfan sulphate, DDD, DDE, HCH isomers, endrin ketone, endrin aldehyde, heptachlor epoxide, methoxychlor. Chloroacetanilides are more sensitive with EI than CI modes with GC/MS (Raina and Hall, 2009;Dagnac et al, 2005;Gabaldon et al, 2002) but can be done with similar detection limits with LC/ ESI+ or APCI+ MS/MS (Dagnac et al, 2005). The transformation products of chloroacetanilides are not analyzed by GC/MS, however chloroacetanilide (eg alachlor, propachlor, metalochlor) analysis is frequently included with analysis of OCs by GC/MS.…”
Section: Gc/ms and Gc/ms/ms Methodsmentioning
confidence: 99%
See 3 more Smart Citations